Equinox and OSGi the power behind Eclipse - McAffer, Jeff (Addison-Wesley Professional, 2009)
A Hands-On Guide to Equinox and the OSGi Framework In OSGI and Equinox: Creating Highly Modular Java"!Systems, three leading experts show developers--for the first time--exactly how to make the most of these breakthrough technologies for building highly modular dynamic systems. You'll quickly get started with Eclipse bundle tooling, create your first OSGi-based system, and move rapidly to sophisticated production development. Next, you'll master best practices and techniques for creating systems with exceptional modularity and maintainability. You'll learn all about OSGi's Declarative Services and how to use them to solve a wide variety of real-world problems. Finally, you'll see everything that you've learned implemented in a complete case study project that takes you from early prototype through application delivery. For every Eclipse developer, regardless of previous experience, this book Combines a complete hands-on tutorial, online sample code at every step, and deep technical dives for working developers Covers the OSGi programming model, component development, OSGi services, Eclipse bundle tooling, server-side Equinox, and much more Offers knowledge, guidance, and best practices for overcoming the complexities of building modular systems Addresses practical issues ranging from integrating third-party code libraries to server-side programming Includes a comprehensive case study that goes beyond prototyping to deliver a fully refined and refactored production system Whatever your application, industry, or problem domain, if you want to build state-of-the-art software systems with OSGi and Equinox, you will find this book to be an essential resource
Print version record
Keywords: Computer software -- Development; Computer software; Development; Electronic resource